Is Group-Based or Individual-Based Intervention more Effective for Quality of Life Outcomes in Children with Developmental Coordination Disorder? A Systematic Review. (4th July 2019) - de Hóra, Niamh; Larkin, Louise; Connell, Amanda
Abstract: Aims: To examine whether group-based or individual-based treatment programs are more effective for quality of life (QOL) outcomes in children with developmental coordination disorder (DCD). Methods: A systematic search of the literature was conducted, in accordance with the PRISMA guidelines. Quality of the papers was assessed using the Modified Downs and Black Checklist. Peer-reviewed clinical experimental studies of children diagnosed with DCD with any QOL related outcome measure were included, of all years, languages, and approaches of intervention. Results: Sixteen studies were identified for inclusion, of mixed methodological qualities (predominantly low). Improvement of QOL with both group-based and individual-based interventions were shown, though large degrees of heterogeneity were observed in study designs, participants, modes of interventions, durations, and outcome measures utilized. Conclusions: The effectiveness of group-based versus individual-based interventions on QOL of children with DCD is unclear. There is a pressing need for a high quality, powered trials, utilizing the randomized control trial paradigm, comparing both intervention approaches with standardized treatment approaches and outcome measures to determine and compare the effect on QOL of children with DCD.